(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Antimicrobial resistance has increased dramatically & to be a serious threat to the treatment of infectious disease on a global basis. As a result morbidity, mortality & economic burden of infections with multiple drug resistance organisms for which there are no effective therapies. Over use of antibiotics in developed nations of paradoxically both misuses of under use in developing nations have contributed to the burden. Objectives: The objective of the study is to identify common microorganisms and to assess their sensitivity to three selected antibiotics. Methods: This observational study was conducted in Armed Forces Institute of Pathology (AFIP), Dhaka, Bangladesh among samples of urine, blood, pus, sputum and throat swab. All of the samples of urine (173), Blood (31), pus (63), sputum (28) and throat swab (14) were tested for culture and sensitivity at AFIP over a period from January 2012 to February 2013. Selected antibiotics were ciprofloxacin, cephradine and cefixime. Results: Commonest organisms found in different samples were Escherichia coli in urine (57.8%), Salmonella typhi in blood (54.8%), Staphylococcus aureus in pus (42.9%), klebsiella in sputum (67.9%) and Streptococcus pyogens in throat swab 03 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 (78.6%). In urine samples, microorganisms were found resistant to cephradine in 95% cases but sensitive to cefixime in 30.4% cases. Microorganisms in blood samples were sensitive to cefixime in 83.3% and Ciprofloxacin in 80.6% cases. Ciprofloxacin, cephradin and cefixime all three antibiotics encountered resistance in 63.5%, 82.5% and 75.8% samples of pus respectively. Among sputum samples organisms were sensitive to ciprofloxacin in 71.4% and cefixime in 64.3% cases whereas resistant to cephradin in 92.9% cases. In organisms of throat swab Cephradine Showed sensitivity in 71.4% cases but cefixime encountered resistance in 57.1% cases. Conclusion: The study reveals an alarming picture of antimicrobial resistance pattern in Bangladesh Armed Forces. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21818 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013